Transgelins: Cytoskeletal Associated Proteins Implicated in the Metastasis of Colorectal Cancer - Liu, Jingwen; Zhang, Yingru; Li, Qi; Wang, Yan (Frontiers in Cell and Developmental Biology, 2020)
Transgelins, including transgelin-1 (T-1), transgelin-2 (T-2), and transgelin-3 (T-3), are a family of actin-binding proteins (ABPs) that can alter the structure and morphology of the cytoskeleton. These proteins function by regulating migration, proliferation and apoptosis in many different cancers. Several studies have shown that in various types of tumor cells, including colorectal cancer (CRC) cells, and in the tumor microenvironment, the expression and biological effects of transgelins are diverse and may transform during tumor progression. Previous researches have demonstrated that transgelin levels are positively correlated with metastasis in CRC, and down-regulating their expression can inhibit this process. In advanced disease, T-1 is a tumor activator with increasing expression, and T-2 expression increases with the progression of CRC. Finally, T-3 is only expressed in neurons and is not associated with CRC. This evidence suggests that T-1 and T-2 are potential biomarkers and therapeutic targets for CRC metastasis.